PENERAPAN METODE QUANTUM LEARNING DALAM PEMBELAJARAN MENULIS PUISI - Fitri Hadianti; Yuliani Sri Hartati; Sary Sukawati (IKIP Siliwangi, 2019)
The background of this research is that some facts found in the field of students cannot express their ideas and imagination into a poem due to difficulties in finding poetic words and the use of less innovative methods. This can be proven from the results of previous student observations showing that some students were less motivated during the learning process, so that students obtained poetry values with less criteria. In connection with this problem, the formulation of the problem of this research is how the results of writing poetry before and after the application of the quantum learning method? This study aims to determine the results of writing poetry using the quantum learning method. The method used is an experimental one-group pretest-posttest design. The average value of the initial test (pretest) obtained was 70.31 while the average value of the final test (posttest) was 80.78, an increase of 11.41%. The SPSS results showed a paired T sample sig test 0,000 <0,05. Therefore it can be concluded if the quantum learning method can be used in poetry learning, because students can make poetry better than before the implementation of the quantum learning method.